Konvergensi Media Dakwah: Studi Kasus Radio Komunitas Ma’dinul Ulum Tulungagung - Panuju, Redi (Jurnal Komunikasi Islam, 2018)
This study discusses the convergence of media conducted by Pesantren Madinul Ulum (Madu) community radio in Campurdarat Tulungagung East Java for promoting Islam. It is interestingly enough to be studied because there are limited availability of channels and the function of community radio constrained by government laws and regulations. Using qualitative approach during January-August 2016, the study has found that this community radio has taken advantage of regulatory gaps to develop a converged media strategy for da’wah. This is conducted by utilizing streaming media, building community radio networks, synergizing with private broadcast radio, setting up private TVs, combining radio broadcasts with online media, and combining on-air with off-air activities.